Definition and characterization of SOX11-derived T cell epitopes towards immunotherapy of glioma - Liu, Yibin; Keib, Anna; Neuber, Brigitte; Wang, Lei; Riemer, Angelika; Bonsack, Maria; Hückelhoven-Krauss, Angela; Schmitt, Anita; Müller-Tidow, Carsten; Schmitt, Michael (International journal of molecular sciences, 2023)
The transcription factor SOX11 is a tumor-associated antigen with low expression in normal cells, but overexpression in glioblastoma (GBM). So far, conventional surgery, chemotherapy, and radiotherapy have not substantially improved the dismal prognosis of relapsed/refractory GBM patients. Immunotherapy is considered a promising strategy against GBM, but there is a fervent need for better immunotargets in GBM. To this end, we performed an in silico prediction study on SOX11, which primarily yielded ten promising HLA-A*0201-restricted peptides derived from SOX11. We defined a novel peptide FMACSPVAL, which had the highest score according to in silico prediction (6.02 nM by NetMHC-4.0) and showed an exquisite binding affinity to the HLA-A*0201 molecule in the peptide-binding assays. In the IFN-γ ELISPOT assays, FMACSPVAL demonstrated a high efficiency for generating SOX11-specific CD8+ T cells. Nine out of thirty-two healthy donors showed a positive response to SOX11, as assessed by the ELISPOT assays. Therefore, this novel antigen peptide epitope seems to be promising as a target for T cell-based immunotherapy in GBM. The adoptive transfer of in vitro elicited SOX11-specific CD8+ T cells constitutes a potential approach for the treatment of GBM patients.
Gesehen am 31.03.2023